Korean Male Celebrity Masculinity Reception in Running Man - Rendy Ardian Muhammad; Dr. Hapsari Dwiningtyas, S.Sos, MA (Interaksi Online, 2016)
This research discussing about Korean male celebrity who have different masculinity when they act in drama and when they are in variety show. When they act in drama, masculine character which shown in the cold-but-care act seems to be stood out. But, when they are in variety show that is shown their real life, male celebrity tend to be feminime, such as disciplining the body. Male celebrity who can represent this masculinity is Song Joong Ki. The aim of this research is to find audiences‟ reception towards Korean male celebrity in Running Man variety show. The reception process covers the text content to search the dominant meaning through preferred reading by using semiotics analysis to find the audiences‟ reception category in dominant, negotiate, and opposition position. This research results show that Song Joong Ki masculinity in his cold-but-care drama character seems to be dominate the audience and even make it as part of important male character in the real life. This result came from the informants‟ reasons to love Korean drama because of the story which reflected the daily life. Then there are three tipe of masculinity which was intepreted by the informants, which is gentleman, ruler, and warrior masculinity. But, the gentleman type is still considered as the masculinity that dominate women. Most of informants interpret Song Joong Ki‟s masculinity on Running Man variety show in dominant position. The informants who are placed in the dominant position thought that Song Joong Ki should treat women well, have a firm body movement, have great general and cooking knowledge, groom his hair, have a soccer hobby, and have fashion appearance that doesn‟t look feminine, because those elements are rigid or have to be owned by men. Informants also interpret other masculinity elements, such as Song Joong Ki‟s make up and weak physical ability in negotiation position. It means that audience can negotiated men who wear make up and don‟t have great physical strength as long as in the suitable context